A profitability assessment of small-scale photovoltaic systems in an electricity market without subsidies. (1st December 2016) - Cucchiella, Federica; D'Adamo, Idiano; Gastaldi, Massimo
Highlights: Net Present Value varies from 437 to 624 € per kW installed. Discounted Payback Time ranges from 4 years to 6 years. Reduction of emissions of 21 tCO2 eq for each kW installed during the 20 years. Break-even point of increase of self-consumption varies from 6% to 13%. The opportunity to keep a 50% of fiscal deduction for 5 years. Abstract: The installation of photovoltaic power plants in 2015 compared to 2014 registered a growth of 25.6%, reaching a cumulative power equal to 229 GW. In developed solar markets, as many European countries, the sector is pushed by the alignment between the electric power demanded and the one offered. Consequently, self-consumption makes consumers active players of the energy transition. Italy is evaluated as a case study in this paper, in fact is the first country in the world where solar energy contributes largely to the national energetic demand. This paper aims to evaluate photovoltaic systems in residential sector without subsidies. Economic and environmental results are proposed and the indicators used are Net Present Value, Discounted Payback Time and Reduction in the Emissions of Carbon Dioxide. Three sizes (3 kW, 6 kW and 20 kW) are evaluated. In addition, a sensitivity analysis of critical variables (investment cost, annual electricity purchase price, annual electricity sales price, opportunity cost, tax deduction unitary, period of fiscal deduction, average annual insolation and percentage of energy self-consumption) demonstrates the robustness of the economic results. Also for environmental evaluation, alternative scenarios are proposed varying the value of emissions released by source energy analysed (photovoltaic, coal, oil and gas). Economic and environmental results suggest that small-scale photovoltaic systems can support the transition towards a sustainable energy mix.